HALAL CERTIFICATION SOCIALIZATION AND UNDERSTANDING IN THE UTILIZATION OF THE FREE SIHALAL PROGRAM IN CHIPS MSMEs IN SOUTH SIBOLGA DISTRICT SIBOLGA CITY - Dewi Sundari Tanjung; Suriana; Riny Viri Insy Sinaga; Rodi Syafrizal; Dini Vientiany; Liza Widya Hasyim (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2025)
One of Of the three main pillars (Tri Dharma) that must be implemented by lecturers in higher education, in addition to education and teaching as well as research and development, community service is an activity carried out by lecturers in collaboration with MSMEs in the Sibolaga district of Sibolga city. The free SI HALAL program from the Halal Product Guarantee Agency (BPJPH) is a great opportunity for Micro and Small Enterprises (MSMEs) to obtain halal certificates at no cost. However, the lack of information and understanding of this certification process is a major obstacle among MSMEs, especially chili chip MSMEs in the South Sibolga District of Sibolga City. This community service activity aims to socialize the importance of halal certification and provide technical understanding in utilizing the free SI HALAL program. The method used is a participatory approach through counseling, interactive discussions, and technical assistance. The results show an increase in understanding and motivation of MSMEs to register their products in the halal certification system. This activity is expected to be the beginning of increasing the competitiveness and business desires of local MSMEs based on halal principles.